ILMU PENDIDIKAN DASAR BERBASIS LOCAL WISDOM - Lubis, Namiroh (PRIMARY EDUCATION JOURNAL (PEJ), 2024)
This study examines the implementation of primary education based on local wisdom in Indonesia. The research aims to explore the integration of local wisdom practices in the curriculum, identify implementation challenges, and formulate efforts to improve the quality of local wisdom-based primary education. The method used is a literature study by analyzing relevant literary sources. The results show that local wisdom can be integrated into various subjects such as Indonesian Language, Science, Civics, Social Studies, and Mathematics through the development of contextual teaching materials, learning media, and teaching methods. The main challenges include limited resources and teachers' understanding of local wisdom. Improvement efforts include teacher professional development, collaboration with local communities, and sustainable education policy support.